New frontiers of oral sciences: Focus on the source and biomedical application of extracellular vesicles - Yu, Wenting; Li, Shengnan; Zhang, Guohao; Xu, Hockin H. K.; Zhang, Ke; Bai, Yuxing (Frontiers in Bioengineering and Biotechnology, 2022)
Extracellular vesicles (EVs) are a class of nanoparticles that are derived from almost any type of cell in the organism tested thus far and are present in all body fluids. With the capacity to transfer “functional cargo and biological information” to regulate local and distant intercellular communication, EVs have developed into an attractive focus of research for various physiological and pathological conditions. The oral cavity is a special organ of the human body. It includes multiple types of tissue, and it is also the beginning of the digestive tract. Moreover, the oral cavity harbors thousands of bacteria. The importance and particularity of oral function indicate that EVs derived from oral cavity are quite complex but promising for further research. This review will discuss the extensive source of EVs in the oral cavity, including both cell sources and cell-independent sources. Besides, accumulating evidence supports extensive biomedical applications of extracellular vesicles in oral tissue regeneration and development, diagnosis and treatment of head and neck tumors, diagnosis and therapy of systemic disease, drug delivery, and horizontal gene transfer (HGT). The immune cell source, odontoblasts and ameloblasts sources, diet source and the application of EVs in tooth development and HGT were reviewed. In conclusion, we concentrate on the extensive source and potential applications offered by these nanovesicles in oral science.